Some Interactive Activities of Communicative Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Communicative language teaching is a method that used to increase students communicative competence. This article describes some interactive activities of communicative language teaching and their usage in teaching process.